Retrospective analysis of 1,211 operated patients due to groin hernia with open surgical approach – single center experience - Marković, Miroslav; Bezmarevic, Mihailo; Ilić, Milan; Dragičević, Marina; Andrić, Aleksandar (Vojnosanitetski pregled, 2020)
Bacground/Aim. Groin hernias are common pathology among men population. Only curative treatment is surgical reparation with various surgical procedures for groin hernia solving. The aim of this study was to evaluate the most prevalent surgical procedures and early postoperative complications after groin hernia reparation in large series of operated patients, and to assess the morphologic characteristics of groin hernias. Methods. The retrospective study included all patients with groin hernia who underwent surgical reparation from 2009 to 2012. In all patients a demographic characteristics, including gender and age, clinical characteristics and hernia type were analyzed. The surgical procedure for hernia solving and early postoperative complications were assessed. Results. The study included 1,211 patients. The male/female ratio was 1,127/84 (p
Keywords: hernia, inguinal; hernia, femoral; men; women; age of onset; incidence; surgical procedures, operative; postoperative complications